1998
DOI: 10.1038/bjc.1998.46
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in plasminogen activation correlate with epithelial cell dysplasia grading in colorectal adenomas

Abstract: Summary Proteases are important for neoplastic invasion but a specific role for the plasminogen activator system in the progression of colorectal epithelial dysplasia to adenomatous lesions remains unclear. Consecutive tissue cryosections of 51 adenomas, 49 distant mucosa samples and five mucosa samples from control subjects were histopathologically analysed for dysplasia grade and tissue type, urokinase plasminogen activator levels and plasminogen activator inhibitor type 1 (PAI-1) using immunosorbent methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Increased expression of uPA and PAI-1 along the adenoma-carcinoma sequence (table 2, 3) is in agreement with Abe et al [13] and Provita et al [29]. In the present study, the number of samples in each stage were not enough for correct use of the ¯2 test, so stages were examined as groups of A/B and C/D and Fisher's exact test was applied.…”
Section: Discussionsupporting
confidence: 74%
“…Increased expression of uPA and PAI-1 along the adenoma-carcinoma sequence (table 2, 3) is in agreement with Abe et al [13] and Provita et al [29]. In the present study, the number of samples in each stage were not enough for correct use of the ¯2 test, so stages were examined as groups of A/B and C/D and Fisher's exact test was applied.…”
Section: Discussionsupporting
confidence: 74%
“…It has been hypothesized that this correlation may be explained by the capacity of PAI-1 to protect the tumour cells from proteolysis at points of invasion [29]. Interestingly, our previous findings suggested that PAI-1, and not uPA, levels found in adenomas and adjacent mucosae could be indicators of postpolypectomy tumour recurrence [14]. The link between PAI-1 levels, poor patient prognosis and possible adenoma recurrence may reflect, in addition to PAI-1 activity as a uPA inhibitor, the existence of dynamic interactions among cells and ECM components, including signalling events, and possibly taking place at a distance from a premalignant or malignant site.…”
Section: Discussionmentioning
confidence: 89%
“…In human colon adenomas, we and others have previously shown that high levels of certain PA members are associated with the early stages of colonic tumour development [13,14]. It is our understanding that these studies were restricted to comparing values obtained from adenomatous versus adjacent mucosa full tissue extracts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies on colorectal adenomas were based on tissue extracts 10,11. According to these studies, before the tissues were taken by colonoscopic biopsy or surgery, it was difficult to predict the presence of colorectal adenomas.…”
Section: Introductionmentioning
confidence: 99%